DUKUNGAN KELUARGA DENGAN KEPATUHAN KUNJUNGAN ANC PADA IBU HAMIL TRIMESTER III - Nurhayati Ningsih; Dyah Siwi Hety; Fitria Edni Wari (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
The purpose of this study was to determine the correlation between family support and compliance with ANC visits in third trimester pregnant women at the Independent Practicing Midwife Amirul Cholifah S.Tr. Keb in Sumberwono Village, Bangsal District, Mojokerto Regency. The results showed that most of the respondents were in the Supporting category, namely 24 people (80%), and most of the respondents were in the Compliant category, namely 20 people (66.7 The results of the Fisher Exact test p value = 0.000 means that there is a correlation between family support and compliance with ANC visits in third trimester pregnant women at Independent Practice Midwife Amirul Cholifah S.Tr. Keb in Sumberwono Village, Bangsal District, Mojokerto Regency. Family support and pregnancy checks are important motivations for pregnant women in the form of compliance with ANC visits to maintain the condition of the mother and the growth of the fetus. It is expected that health workers will provide education and counseling about ANC to pregnant women so that families pay more attention to the physiological and psycholoical conditions of pregnant women